Mono‐ and Dianion of a Bis(benzobuta)tetraazapentacene Derivative. Issue 42 (3rd July 2019) - Ji, Lei; Hahn, Sebastian; Biegger, Phillip; Reiss, Hilmar; Han, Jie; Friedrich, Alexandra; Krummenacher, Ivo; Braunschweig, Holger; Moos, Michael; Freudenberg, Jan; Lambert, Christoph; Dreuw, Andreas; et al.
Abstract: A bis(benzobuta)tetraazapentacene derivative was reduced to its radical anion and its dianion, using potassium [18]crown‐6 anthracenide in THF. Both reduced species were characterized by UV/Vis spectroscopy of the isolated species and by spectroelectrochemistry. Two distinct single‐crystal structures of the dianion and an EPR spectrum of the radical anion were obtained. Contrary to other azaacenes, the lowest energy absorption in the UV/Vis spectrum of the dianion is redshifted in comparison to that of the neutral compound. Abstract : Reduction : A bis(benzobuta)tetraazapentacene derivative was reduced to its radical anion and its dianion, using potassium [18]crown‐6 anthracenide in THF. Both reduced species were characterized by UV/Vis spectroscopy of the isolated species and by spectroelectrochemistry (see graphic).